PENGUATAN LITERASI PANGAN: EDUKASI PROTEIN HEWANI DAN NABATI BAGI SISWA PELAJAR DI MALAYSIA - Ertika Fitri Lisnanti; Erlin Widya Fatmawati; Sri Luayi; Riski Slamet Hartanto; Muhammad Alfa Niam (Jurnal Abdi Insani, 2026)
Balanced nutrition is a crucial factor in supporting the growth and development of elementary school children. However, students’ understanding of animal- and plant-based protein sources remains low due to the lack of engaging and contextual nutrition learning methods. Food literacy plays an important role in shaping nutritional awareness from an early age, especially for Indonesian students abroad who face cross-cultural food environments. This international community service program aimed to enhance the food literacy of students at the Indonesian School of Kuala Lumpur (SIKL) through interactive education on animal and plant-based protein sources. The activity was conducted from August 26–30, 2025, involving 60 elementary school students. The implementation method employed an educational approach based on interactive sticker games that combined visual and kinesthetic elements. Evaluation was carried out by comparing students’ ability to classify food sources before and after the activity using descriptive percentage analysis. The results showed a significant increase in students’ understanding, from 45% to 90% after the activity. Moreover, students demonstrated high enthusiasm and active participation throughout the learning process, which strengthened both cognitive and social aspects. The visual-kinesthetic approach proved effective in correcting conceptual misunderstandings and improving long-term memory retention. This program also strengthened international academic collaboration and contributed to the achievement of SDG 2 (Zero Hunger) and SDG 4 (Quality Education). Therefore, participatory game-based learning can serve as an effective and enjoyable strategy for fostering children’s food literacy in cross-national elementary education settings. Keywords: food literacy, animal protein, plant-based protein, interactive learning, international